PILIHAN HUKUM WARIS BAGI ORANG DI INDONESIA BERAGAMA ISLAM - Bambang Yunarko (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Authoritative give and break the heir case for Indonesia people which believe in the Islam based interest of absolute Religion Court, Section 49 sentence 1 Number Law 7 Year 1989, residing in Religion Court, while choice of hereditary law for Indonesia people which believe in the Islam pursuant to number 2 sixth paragraph public Clarification of Number Law 7 Year 1989 can only be done outside Jurisdiction Body.